Xpert MTB/XDR: a 10-color reflex assay suitable for point-of-care settings to detect isoniazid, fluoroquinolone, and second-line-injectable-drug resistance directly from mycobacterium tuberculosis-positive sputum - Cao, Yuan; Parmar, Heta; Gaur, Rajiv L.; Lieu, Deanna; Raghunath, Shobana; Via, Nova; Battaglia, Simone; Cirillo, Daniela M.; Denkinger, Claudia M.; Georghiou, Sophia; Kwiatkowski, Robert; Persing, David; et al. (Journal of clinical microbiology, 2021)
We describe the design, development, analytical performance, and a limited clinical evaluation of the 10-color Xpert MTB/XDR assay (CE-IVD only, not for sale in the United States). This assay is intended as a reflex test to detect resistance to isoniazid (INH), fluoroquinolones (FLQ), ethionamide (ETH), and second-line injectable drugs (SLIDs) in unprocessed sputum samples and concentrated sputum sediments which are positive for Mycobacterium tuberculosis. The Xpert MTB/XDR assay simultaneously amplifies eight genes and promoter regions in M. tuberculosis and analyzes melting temperatures (Tms) using sloppy molecular beacon (SMB) probes to identify mutations associated with INH, FLQ, ETH, and SLID resistance. Results can be obtained in under 90 min using 10-color GeneXpert modules. The assay can differentiate low- versus high-level resistance to INH and FLQ as well as cross-resistance versus individual resistance to SLIDs by identifying mutation-specific Tms or Tm patterns generated by the SMB probes. The assay has a limit of detection comparable to that of the Xpert MTB/RIF assay and successfully detected 16 clinically significant mutations in a challenge set of clinical isolate DNA. In a clinical study performed at two sites with 100 sputum and 214 clinical isolates, the assay showed a sensitivity of 94% to 100% and a specificity of 100% for all drugs except for ETH compared to that of sequencing. The sensitivity and specificity were in the same ranges as those of phenotypic drug-susceptibility testing. Used in combination with a primary tuberculosis diagnostic test, this assay should expand the capacity for detection of drug-resistant tuberculosis near the point of care.
Gesehen am 07.04.2021